1993
DOI: 10.1002/em.2850210402
|View full text |Cite
|
Sign up to set email alerts
|

Genetic toxicity of fluoride

Abstract: F- is not mutagenic in standard bacterial systems, but produces chromosome aberrations and gene mutations in cultured mammalian cells. Although there is disagreement in the literature concerning the ability of F- to induce chromosome aberrations in cultured human and rodent cells, the weight of the evidence leads to the conclusion that F- exposure results in increased chromosome aberrations in these test systems. NaF induced primarily chromatid gaps and chromatid breaks, indicating that the rodent cells are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 56 publications
1
17
0
1
Order By: Relevance
“…This is not surprising, since overwhelmingly the literature on NaF supports the conclusion that it is primarily clastogenic and not mutagenic. NaF is only readily detected in "mutations" like L5178Y at genetic loci that can tolerate larger deletions, not HGPRT unless very high doses and long incubations such as used by Crespi and colleagues (1990) are employed (Zeiger et al, 1993). Results presented in this paper support the contention that the effects of sodium fluoride in humans probably do not represent any serious mutagenic or carcinogenic threat.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…This is not surprising, since overwhelmingly the literature on NaF supports the conclusion that it is primarily clastogenic and not mutagenic. NaF is only readily detected in "mutations" like L5178Y at genetic loci that can tolerate larger deletions, not HGPRT unless very high doses and long incubations such as used by Crespi and colleagues (1990) are employed (Zeiger et al, 1993). Results presented in this paper support the contention that the effects of sodium fluoride in humans probably do not represent any serious mutagenic or carcinogenic threat.…”
Section: Discussionsupporting
confidence: 65%
“…Carcinogenic effects of NaF were suggested by the results of Tsutsui and co-workers (1984c) and Lasne and co-workers (1988), who demonstrated that NaF causes neoplastic transformation of SHE cells and BALB/3T3 cells in vitro, as well as by results obtained by Jones and co-workers (1988), who found that NaF can promote the frequency of morphologically transformed cell clones previously initiated with either procarcinogens or directacting agents. A summary report on results of genotoxicity testing of fluoride in microbial test systems and in vitro and in vivo mammalian test systems has been published (Zeiger et al, 1993). Crespi and co-workers (1990) suggested that NaF induces gene-locus mutations at the thymidine kinase and hypoxanthineguanine phosphoribosyl transferase (HGPRT) loci in human lymphoblastoid cells treated with toxic concentrations of NaF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to F -increases the production of superoxide as a consequence of hydrogen peroxide metabolism, inducing peroxinitrate, hydroxyl radicals increasing oxidative stress (Barbier et al, 2010;GarciaMontalvo et al, 2009;Chinoy, 2003), and inducing lypoperoxidation of membranes, apoptosis and DNA damage (Wang et al, 2007). The clinical application of NaF induced genotoxicity on the oral epithelium in acute exposition according to Zeiger et al (1993). Tiwari and Rao (2010) considered F -as a mutagenic agent that even in low concentrations can increase the induction of chromosomal aberrations.…”
Section: Discussionmentioning
confidence: 99%
“…Both negative and positive results on cytogenetic changes -mostly chromosomal aberrationshave been reported with sodium monofluorophosphate in human lymphocytes and leukocytes (Zeiger et al, 1993).…”
Section: In Vitro Studiesmentioning
confidence: 97%